Do natural enemies explain fluctuations in low‐density spruce budworm populations?. Issue 9 (30th July 2018) - Bouchard, Mathieu; Martel, Véronique; Régnière, Jacques; Therrien, Pierre; Correia, David Laginha Pinto
Abstract: Understanding the causal pathways through which forest insect outbreaks are triggered is important for resource managers. However, detailed population dynamics studies are hard to conduct in low‐density, pre‐outbreak populations because the insects are difficult to sample in sufficient numbers. Using laboratory‐raised larvae installed in the field across a 1, 000 km east–west gradient in Québec (Canada) over an 11‐yr period, we examined if parasitism and predation were likely to explain fluctuations in low‐density spruce budworm ( Choristoneura fumiferana ; SBW) populations. Parasitism rates by the two main larval parasitoid species, Elachertus cacoeciae and Tranosema rostrale, peaked during different years. This suggests that temporal fluctuations in overall parasitism were partly buffered by compensatory dynamics among parasitoid species. Still, spatial covariance analyses indicate that the residual interannual variation in parasitism rates was substantial and correlated over large distances (up to 700 km). On the other hand, interannual variation in predation rates was not spatially correlated. Piecewise structural equation models indicate that temporal variation in parasitism and predation does not influence temporal variation in wild SBW abundance. Spatially, however, SBWs installed in warmer locations tended to show higher parasitism rates, and these higher rates correlated with lower wild SBW population levels. Overall, the results indicate that large‐scale drops in parasitism occur and could potentially contribute to SBW population increases. However, during the period covered by this study, other factors such as direct effects of weather on SBW larval development or indirect effects through host tree physiology or phenology were more likely to explain large‐scale variation in wild SBW populations.